2010
DOI: 10.1111/j.1466-7657.2010.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Empathy: the effects of undergraduate nursing education in Turkey

Abstract: The findings have shown that empathic skills developed during undergraduate nursing education. However, empathetic tendency has shown a decline during these educational years. The decrease in empathetic tendency during undergraduate education should be taken into account, and educators and researchers should consider possible reasons for this outcome. Further research is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 20 publications
0
50
1
7
Order By: Relevance
“…38 This finding runs counter to the popular belief that nurses are the most empathetic health professionals. 39 Those results must be taken with precaution considering that our group of nurses simultaneously displayed a higher level of psychological distress than the general population of Canada, 40 together with a lower level of psychological wellbeing. Most studies of mental health in nurses focus on psychological distress, 20,41 but few consider psychological well-being.…”
Section: Discussionmentioning
confidence: 93%
“…38 This finding runs counter to the popular belief that nurses are the most empathetic health professionals. 39 Those results must be taken with precaution considering that our group of nurses simultaneously displayed a higher level of psychological distress than the general population of Canada, 40 together with a lower level of psychological wellbeing. Most studies of mental health in nurses focus on psychological distress, 20,41 but few consider psychological well-being.…”
Section: Discussionmentioning
confidence: 93%
“…Empathic skills are essential for the provision of effective nursing care (7); they are teachable, and important for cooperation-based relationships. It has been reported that the nature of the nursing profession requires nurses to have these skills (8-10). In their study, Reynolds & Scott (9) emphasized that nurses who are able to approach their patients empathetically can better understand their reactions to health problems, as well as the purpose and source of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…McKenna et al (2012) found that nursing students in Australia had a high empathy level with a mean of 107.34 within a possible range of scores of 20-140 on the Jefferson Scale of Physician Empathy (Health Professional Version). A longitudinal study on undergraduate nursing students in Turkey found that students had an increase in empathic skills but a decrease in empathic tendency throughout their education (Ozcan et al, 2010). Ward et al (2012) also found that undergraduate nursing students decreased their empathy with increased exposure to patients.…”
Section: Empathy Of Nursing Studentsmentioning
confidence: 98%